Perdagangan Saham di Bursa Efek: Konsep, Mekanisme, dan Perspektif Islam: Stock Trading on the Stock Exchange: Concepts, Mechanisms and Islamic Perspectives - Azwar, Azwar; Andi Wawan Mulyawan; Hamzah Khaeriyah; Abdi Wijaya (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
This study aims to provide a comprehensive understanding of stock trading from conceptual, operational, and normative perspectives based on Indonesian positive law and Islamic jurisprudence (fiqh). The research employs a qualitative-descriptive approach using library research methods by examining legal literature, DSN-MUI fatwas, and scholarly references related to stocks and capital markets. The analysis was conducted through document review and content analysis of applicable regulations and Islamic legal opinions. The findings indicate that, under Indonesian law, stocks are legal instruments protected by legislation and play a vital role in the capital market system. From an Islamic perspective, stock trading is permissible as long as it avoids elements of riba (usury), gharar (uncertainty), and maysir (gambling), and adheres to sharia principles. DSN-MUI fatwas serve as key references in determining the permissibility of sharia-compliant stocks and transaction mechanisms. Thus, stock trading can be conducted lawfully and ethically in accordance with national legal frameworks and Islamic principles.